Qualitätsmanagement aus juristischer Sicht. - Ruland, A.; Becker, C. (Der Urologe A, 2019)
The aim of quality management in medicine must be to increase the safety of treatment, to optimize the treatment results, but also to confirm economic justifiability. Participation in multiagency quality assurance measures should create the possibility to assess the quality of the services offered compared with other service providers and to recognize and correct corresponding deficits. Comparative examinations and assessments should serve to improve the quality of the results. The benefits of quality management as an important approach to promoting patient safety should be made known to all stakeholders. Patient-oriented process optimization and patient satisfaction are the focus. Furthermore, quality management should help increase the satisfaction of everyone involved in the process.